Chylous Ascites and Lymphoceles: Evaluation and Interventions - Santos, Ernesto; Moussa, Amgad M. (Seminars in Interventional Radiology, 2020)
Kinmonth introduced lymphangiography in 1955 and it became an important tool in the diagnosis and treatment of malignant disease. The technique, based on bipedal approach, was difficult and time-consuming which limited its use in clinical practice. Cope is the father of percutaneous lymphatic interventions and he was the first person to access and intervene on the lymphatic system. After his initial work published on 1999, there has been an expansion of the lymphatic embolization techniques, particularly since the development of intranodal lymphangiography and advance lymphatic imaging. This article is focused on the evaluation and management of postoperative chylous ascites and lymphoceles. Their incidence is growing due to longer survival of cancer patients and more radical surgical approaches, leading to an increased morbidity and mortality in this patient population. Minimally invasive percutaneous lymphatic embolization is becoming a first-line therapy in patients with postoperative lymphatic leakage.
Keywords: chylous ascites; lymphocele; lymphangiography; embolization; interventional radiology